Polarization and reflectance are linked to climate, size and mechanistic constraints in a group of scarab beetles - Laura Ospina-Rozo; Iliana Medina; Andrew Hugall; Katrina J. Rankin; Nicholas W. Roberts; Ann Roberts; Andrew Mitchell; Chris A. M. Reid; Adnan Moussalli; Devi Stuart-Fox (Scientific Reports)
Abstract Beetles exhibit an extraordinary diversity of brilliant and colourful appearances and optical effects invisible to humans. Their underlying mechanisms have received some attention, but we know little about the ecological variables driving their evolution. Here we investigated environmental correlates of reflectivity and circular polarization in a group of optically diverse beetles (Scarabaeidae–Rutelinae). We quantified the optical properties of 261 specimens representing 46 species using spectrophotometry and calibrated photographs. Then, we examined associations between these properties and environmental variables such as temperature, humidity and vegetation cover, controlling for body size and phylogenetic relatedness. Our results showed larger beetles have higher visible reflectivity in drier environments. Unexpectedly, near-infrared (NIR) reflectivity was not correlated with ecological variables. However, we found a correlation between humidity and polarization (chiral nanostructures). We identified trade-offs between optical properties: beetles without polarization-associated nanostructures had higher NIR reflectivity. By contrast, visible reflectivity was negatively correlated with the accumulation of pigments such as melanin. Our study highlights the value of a macroecological approach for testing alternative hypotheses to explain the diversity of optical effects in beetles and to understand the link between structure and function.